Generalized Hybrid Censored Reliability Acceptance Sampling Plans for the Weibull Distribution. Issue 4 (2nd October 2018) - Sen, Tanmay; Bhattacharya, Ritwik; Tripathi, Yogesh Mani; Pradhan, Biswabrata
SYNOPTIC ABSTRACT: This work considers determination of reliability acceptance sampling plans (RASPs) for the Weibull distribution under generalized hybrid censoring schemes (GHCSs). Sample size and an acceptability constant are determined for specified producer's and consumer's risks, using the asymptotic normality of the maximum likelihood estimators of model parameters. A simulation study is undertaken to verify whether the RASPs meet the specified risks for finite sample size. Optimum RASPs are obtained based on a variance minimization criterion subject to a cost constraint. Suitable algorithms are proposed for computation of optimum RASPs. One data set is analyzed for the purpose of illustration in real-life application.